WARFARIN-INDUCED ALOPECIA: A RARE CASE REPORT - A, Saurab; Ommurugan, Balaji; Priya, Amita; Patil, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â As new drugs are developed everywhere worldwide to combat many diseases, side effects due to drugs are always a matter of concern. Warfarin is indicated for the treatment of venous thromboembolism over many decades and it is always associated with many side effects ranging from bleeding complications, gastrointestinal disturbances to skin necrosis. Hair fall with oral anticoagulants had always been a matter of debate and concern and so far, only very few case reports have been published on warfarin-induced hair loss. Hence, we report a case of warfarin-induced alopecia in a 39-year-old male in a tertiary care hospital in Southern India.